Oddman has given the right answer to your question and i am satisfied there solve. Buddies you must to visit there homepage gethelpwindows10.com and use there given services.

42 - 9 = 49 is a false subtraction sentence.

If you mean 42 - g = 43, you can subtract 42 from both sides of the equation to get

(42 - g) - 42 = (43) - 42

0 - g = 1

Now you can multiply by -1 on both sides

(-1)(-g) = (-1)(1)

g = -1

Check

42 - (-1) = 43

42 + 1 = 43 (yes)

If you mean 42 - g = 43, you can subtract 42 from both sides of the equation to get

(42 - g) - 42 = (43) - 42

0 - g = 1

Now you can multiply by -1 on both sides

(-1)(-g) = (-1)(1)

g = -1

Check

42 - (-1) = 43

42 + 1 = 43 (yes)